Интертекстуальные отсылки в рассказе Л. Петрушевской «Новые Робинзоны» - Tóthová, Laura (SlavVaria, 2023)
Intertextual references in the story The New Robinson Crusoes by L. Petrushevskaya. The article explores how L. Petrushevskaya uses intertextual codes in her works and how she contextualizes social phenomena in the story New Robinsons, in which three layers are distinguished: archetypal plots and archetypes, works of Russian literature of the 20th century and cultural imprints of specific historical events. On the first layer a deconstruction of D. Defoe’s novel Robinson Crusoe, on the second layer a parallel to Solzhenitsyn's novel “Matryonin Dvor”, on the third layer various important historical events, such as the Spanish Civil War as well as the entry of Soviet tanks into Vilnius in 1991.